PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAGERIAL DENGAN PENGAWASAN INTERNAL SEBAGAI VARIABEL PEMODERASI (STUDI PADA PEMERINTAH KABUPATEN BUNGO) - Machfia Win Hidayati (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The purpose of this study was to determine participation in budgeting, goal clarity and organizational commitment affect either partially or simultaneously to managerial performance SKPD,  and to investigate the internal control will moderate the influence of budget participation, budget goal clarity and commitment to managerial performance SKPD, This research is descriptive kuantitatif.dan research sites are Bungo By taking 56 respondents from 60 SKPD. On the hypothesis of the test equipment is for partial t test and F test to test the effect simultaneously, while for hypothesis testing to see the effect of moderating two variables used analysis absolute difference. The study states that simultaneously all independent variables affect the performance of managerial and partially only research budget goal clarity has no effect on managerial performance SKPD, and participation in budgeting and organizational commitment influence managerial performance SKPD. Internal supervision may moderate the effects of participation in the budget, the budget clarity and organizational commitment to managerial performance SKPD.Keywords: Participation in budget preparation, budget goal clarity of organizational commitment, internal control, managerial performance SKPD